An Overview of RFID in Libraries (International Journal of Innovative Research in Computer Science & Technology, 2020)
In a library, circulation and shelving of  reading materials is a time-consuming task that consumes  the majority of the library staff's time. Because RFID  minimises the time it takes to undertake circulation tasks,  it is a viable solution to this problem. The benefits and  limitations of RFID usage in libraries are discussed in this  article, as well as the components and technological  aspects of a modern RFID library system. It also looks at  the existing level of RFID deployment in Indian libraries  and makes some suggestions. Applications that use radio  frequency identification (RFID) to provide massive access,  huge data storage, as well as reprogramming. RFID  technology may improve operational efficiency and  accuracy. One of the most important variables determining  whether RFID will be adopted in libraries is the cost.  Despite the fact that RFID has increased library efficiency,  the core of the library service has not altered.
Keywords: Antenna; Libraries; RFID; Radio Frequency Identification; Readers